The othering concept towards the church in the Amrika Allati Ra’aytu Travelogue by Sayyid Qutb - Firuz-akhtar Lubis,; Nur Asyiqin Zohkarnain, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Sayyid Qutb was a great thinker in Islamic religious matters. His writings and ideology were often used as reference by the Muslim community in the 20th century. Each piece of his writings contains implicit meanings that require in-depth understanding. However, his travelogue entitled Amrika Allati Ra’aytu or its English translation The America I Have Seen in the Scale of Human Values has received less attention than his other works. This travelogue is unique in that it mainly narrates the primitive side of the church institution in the United States (U.S), unlike his other works that are more neutral. This study, therefore, analysed this primitive perspective based on a selected theory known as othering theory. This qualitative research used the documentation and content analysis methods. The result of this study shows that while this travelogue mostly presents primitive connotation towards the church institution; based on the othering concept, it is an action of Sayyid Qutb as a nationalist who defended the Muslim community in Egypt at that time from being continuously colonised by Western ideologies. This study is hoped to provide a new perspective in religious studies, particularly from the aspect of religious criticism.